Investigations on the Droplet Impact onto a Spherical Surface with a High Density Ratio Multi-Relaxation Time Lattice-Boltzmann Model (Communications in Computational Physics, 2014)
In the current study, a two-dimensional multi-relaxation time (MRT) latticeBoltzmann model which can tolerate high density ratios and low viscosity is employedto simulate the liquid droplet impact onto a curved target. The temporal variation ofthe film thickness at the north pole of the target surface is investigated. Three differenttemporal phases of the dynamics behavior, namely, the initial drop deformation phase,the inertia dominated phase and the viscosity dominated phase are reproduced andstudied. The effect of the Reynolds number, Weber number and Galilei number on thefilm flow dynamics is investigated. In addition, the dynamic behavior of the dropletimpact onto the side of the curved target is shown, and the effect of the contact angle,the Reynolds number and the Weber number are investigated.